DISTRIBUTION OF PANTOTHENIC ACID IN FISH. - CHHATBAR, SUDHIR K; VELANKAR, N K (Fishery Technology, 2017)
The distribution of pantothenic acid in free and boundforms in various fish species is reported. It is observed thatthe fish muscle contains on an average about 12.0fi g. pantothenicacid per g. About 60% of the panthothenic acid is presentin the bound form as coenzyme A in the fish skeletal muscle.